Renal Transplantation in Patients with Hereditary Fibrinogen Amyloidosis. (July 2018) - Tavares, Isabel; Silvano, José; Pereira, Pedro Rodrigues; Silva, Roberto; Lobato, Luísa; Henriques, António Castro; Escada, Luís; Macário, Fernando; Sampaio, Susana
Abstract : Introduction: Fibrinogen A alpha-chain (AFib) amyloidosis is an autosomal dominant disease that typically presents with nephropathy. The p.Glu545Val fibrinogen A alpha-chain gene (FGA) variant is the cause of AFib amyloidosis that was identified in northern Portugal and accounts for the disease in 17 families. Renal transplantation is a supportive therapy with unexpected early complications. Materials and Methods: Outcomes following renal transplantation were evaluated in six consecutive patients with AFib E526V (p.Glu545Val) amyloidosis that received a kidney transplant between 1996 and 2017 in three kidney transplant centers. Results: Three males and three females underwent renal transplantation at a mean age of 60.8±5.9 years. The first kidney transplant was performed in 1996 and the patient lived during 16 years with a functioning kidney. The other patients were transplanted in 2014 (1), 2015 (1), 2016 (1) and 2017 (2). One patient underwent transplantectomy on post-transplantation day 8 due to uncontrolled bleeding associated with a small dehiscence of the arterial allograft anastomosis; the patient exhibited neither histological findings of acute rejection nor evidence of amyloid deposition in the allograft. Twenty days after returning to haemodialysis, this patient underwent urgent nephrectomy due to spontaneous native kidney rupture. There was massive amyloid deposition in the glomeruli with no interstitial, vascular or capsular involvement. Another patient underwent a right coronary percutaneous intervention on post-transplantation day 3 due to acute coronary syndrome. Six months later, he underwent transplantectomy due to allograft obstructive ureterohydronephrosis and returned to haemodialysis. The other three patients have no clinical evidence of amyloid recurrence in the allograft. Discussion and Conclusion: AFib amyloidosis is an increasing cause of chronic kidney disease among kidney transplant recipients in Portugal. Our experience with renal transplantation in patients with AFib amyloidosis is limited and is characterized by short-term post-transplantation complications that led to graft loss in two of six cases. In contrast, one of our patients died 16 years after renal transplantation with a functioning graft. Emerging therapies at the amyloidogenesis cascade level that seek to prevent the formation and promote the clearance of amyloid deposits are potentially novel agents, which might change the therapeutic approach to this disease in the future.